Health policies for the LGBT population, cultural competence, and the organization for access to services: : A systematic review - Freitas, Camila Amaral Moreno; Carvalho, Vinícius Nunes; Jesus, Naila Neves de; Bezerra, Marcos Vinícius da Rocha; Santos, Adriano Maia dos; Kochergin, Clavdia Nicolaevna; Prado, Nília Maria de Brito Lima (Cadernos de Gênero e Diversidade, 2022)
This is a literature review that aimed to analyze the scope of public health policies for the LGBT population in different countries on the European continent, North America and Oceania in order to identify the differences and similarities in content and organization of services and programs. 24 articles were selected to compose the corpus of this review. The results demonstrated the existence of different scopes of health policies for LGBT in the USA, Canada, Australia and the United Kingdom and a heterogeneous result with regard to the objective of the implementation of actions, with emphasis on directions related to LGBT aging, smoking cessation, control of alcohol and other drugs use, as well as cancer and HIV care policies. There was a predominance of approaches limited to the diseases (or unsafe sexual practices, instead focus to comprehensive health care to the LGBT population at different levels of complexity in health care. Furthermore, cultural differences imply granting comprehensive or restrictive health rights. It's necessary to improve the design of public health promotion policies for gender and sexual diversity that are more inclusive and concatenated with other determinants that permeate comprehensive health care.